2020
DOI: 10.1111/jfs.12767
|View full text |Cite
|
Sign up to set email alerts
|

The impacts of water and ethanolic extracts of propolis on vacuum packaged sardine fillets inoculated with Morganella psychrotolerans during chilly storage

Abstract: The impacts of water and ethanolic extracts of propolis at a dose of 0.4 or 0.8% on vacuum packaged sardine fillets inoculated with Morganella psychrotolerans DSM 17886 during storage at 3 ± 1°C for 15 days were investigated. All fish groups were inoculated with M. psychrotolerans (108 cfu/ml) at a rate of 1%. Sensory, colorimetric, chemical analysis (total volatile basic nitrogen, thiobarbituric acid, peroxide values, and free fatty acids), pH value, and microbiological analysis (viable mesophilic and psychro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 41 publications
2
9
1
Order By: Relevance
“…Synthetic preservatives are reported to delay the lipid peroxidation process and increase the shelf life of foods. But, the synthetic additives can be affected consumer health, so consumers are tend to avoid foods prepared with chemical preservatives (Yazgan et al, 2020). Propolis is a natural product collected by honeybees from plants especially owers and buds.…”
Section: Introductionmentioning
confidence: 99%
“…Synthetic preservatives are reported to delay the lipid peroxidation process and increase the shelf life of foods. But, the synthetic additives can be affected consumer health, so consumers are tend to avoid foods prepared with chemical preservatives (Yazgan et al, 2020). Propolis is a natural product collected by honeybees from plants especially owers and buds.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, in this study, to avoid the direct use of propolis, a mixture of gelatin film-propolis was prepared that could exhibit reasonable sensory characteristics with extended shelf life. There are some studies related with the effects of both ethanolic and water extracts of propolis in fish fillets [10,11]. However, the incorporation of edible films with propolis extract is limited and conducted on chitosan films [12].…”
Section: Introductionmentioning
confidence: 99%
“…The obtained results for CM + PLE groups were considerably lower than the accepted limit of 7 log cfu/g (ICMSF, 1986). Propolis liquid extract treatments inhibited the growth of psychrotrophic bacteria count, a fact which has been confirmed by many researchers, such as Jafari et al (2017), Fadıloğlu and Emir Çoban (2018) and Yazgan et al (2020). According to these findings, it was concluded that chia mucilage coating, like other materials used to coat fish and fish products, has a significant effect on decreasing the psychrophilic bacteria count.…”
Section: Resultsmentioning
confidence: 62%